The effects of short-term exercise on the cognitive orientation for health and adjustment in ... - Greif H; Kreitler S (Behavioral Medicine)
Previous studies have shown that cardiovascular patients benefit from exercise. The explanations are partly physical and partly psychological, yet evidence for the latter is contradictory, possibly because only selected samples start and maintain prolonged exercising. The authors examined psychological effects of short-term exercise started as soon as possible after myocardial infarction, focusing on the motivation for health of 62 male and female patients who had had a myocardial infarction 7 to 10 days earlier. Patients were divided into those who exercised for a week in a recovery camp, those who merely stayed for a week in the camp, and those who did not stay in the camp. Results of before and after tests indicated that two scores of the motivation for health (goals and norms) of patients in the exercise group increased, even when complications, former exercising, and infarct location were considered. A month later, 53 of the patients completed a cardiological adjustment questionnaire. The exercise group scored higher than the others on 8 of 9 domains, including subjective health state, sexuality, and work. Even short-term supervised exercise, if done immediately after infarction, has a great potential for beneficial psychological effects, the authors concluded.